Tradisi Seni Tari Pencak Silat Depok Sruti Dalam Rangkaian Upacara di Pura Mas Penyeti Buleleng: (Kajian Pendidikan Agama Hindu) - Sedana, I Made (Jayapangus Press, 2023)
The temple is one of the symbols or symbols of the universe created by Ida Sang Hyang Widhi Wasa, by Hindus it is seen as the stana of Ida Sang Hyang Widhi Wasa and His prabhawa and the ancestral holy spirit with the function of the temple as a means to worship Ida Sang Hyang Widhi Wasa and his family. all his manifestations. Pura Mas Penyeti has several unique features because at each piodalan, a drum called gong kedencong is performed. This kedencong gong percussion is a type of gong that is different from other gongs that accompany the Depok Sruti pencak silat dance. This research is a qualitative research with an ex post facto approach. The informant determination technique was based on purposive sampling and Snow Ball techniques and data collection techniques, namely observation, interview and documentation techniques. data analysis using Ethnographic Content Analysis (ECA) which is carried out with data reduction activities, including: data disposal, data transformation, data grouping, data presentation, inference and verification, and checking data validity. The function of the Depok Sruti Pencak Silat dance performance at the Mas Penyeti Temple can be broadly divided into five, namely: (1) Religious function. (2) Functions and Values ​​of Hindu Education. (3) The function of cultural preservation. The Depok Sruti Pencak Silat Dance tradition at Mas Penyeti Temple has many noble values, especially the value of Hindu education which has been passed down well, these values ​​are internalized to the next generation of temple owners.